Dynamics of Inflation and Economic Growth in Nigeria: 1970 - 2005 - Adegboye, Abiodun Adewale (2015)
The study examined the nexus between inflation and economic growth in the Nigerian economy. It specifically analyzed the dynamic and causal interactions between the two variables; determined the critical level of inflation for target growth rate and examined the extent to which money supply had been driving inflation-growth process in Nigeria. This was with a view to providing empirical evidence for the rationality behind inflation targeting framework in the Nigerian economy.